Do Parents Work More When Children Start School? Evidence from the Netherlands - Lisette Swart; Wiljan Van den Berge; Karen van der Wiel (Institute of Labor Economics (IZA), 2019)
When children start school, parents save time and/or money. In this paper, we empirically examine the impact of these changes to the family's budget constraint on parents' working hours. Labor supply is theoretically expected to increase for parents who used to spend time taking care of their children, but to decrease for fulltime working parents because of an income effect: child care expenses drop. We show that the effect of additional time dominates the income effect in the Netherlands, where children start school (kindergarten) for approximately 20 hours a week in the month that they turn 4. Using detailed administrative data on all parents, we find that the average mother's hours worked increases by 3% when her youngest child starts going to school. For their partners, who experience a much smaller shock in terms of time, the increase in hours worked is also much smaller at 0.4%.
Keywords: J13; J22; 330; labor supply; starting school; child care